Psychometric Evaluation of the German Version of the Demoralization Scale-II and the Association Between Demoralization, Sociodemographic, Disease- and Treatment-Related Factors in Patients With Cancer - Koranyi, Susan; Hinz, Andreas; Hufeld, Julia M.; Hartung, Tim J.; Quintero Garzón, Leonhard; Fendel, Uta; Letsch, Anne; Rose, Matthias; Esser, Peter; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2021)
Objective: To test the psychometric properties, internal consistency, dimensional structure, and convergent validity of the German version of the Demoralization Scale-II (DS-II), and to examine the association between demoralization, sociodemographic, disease- and treatment-related variables in patients with cancer. Methods: We recruited adult patients with cancer at a Psychosocial Counseling Center and at oncological wards. Participants completed the 16-item DS-II, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Screener-2 (GAD-2), Distress Thermometer (DT), and Body Image Scale (BIS). We analyzed internal consistency of the DS-II using Cronbach`s Alpha (α). We tested the dimensional structure of the DS-II with Confirmatory Factor Analyses (CFA). Convergent validity was expressed through correlation coefficients with established measures of psychological distress. The associations between demoralization, sociodemographic, disease- and treatment-related variables were examined with ANOVAs. Results: Out of 942 eligible patients, 620 participated. The average DS-II total score was M = 5.78, SD = 6.34, the Meaning and Purpose subscale M = 2.20, SD = 3.20, and the Distress and Coping Ability subscale M = 3.58, SD = 3.45. Internal consistency ranged from high to excellent with α = 0.93 for the DS-II total scale, α = 0.90 for the Meaning and Purpose subscale, and α = 0.87 for the Distress and Coping Ability subscale. The one-factor and the two-factor model yielded similar model fits, with CFI and TLI ranging between 0.910 and 0.933, SRMR < 0.05. The DS-II correlated significantly with depression (PHQ-9: r = 0.69), anxiety (GAD-2: r = 0.72), mental distress (DT: r = 0.36), and body image disturbance (BIS: r = 0.58). High levels of demoralization were reported by patients aged between 18-49 years (M = 7.77, SD = 6.26), patients who were divorced/ separated (M = 7.64, SD = 7.29), lung cancer patients (M = 9.29, SD = 8.20), and those receiving no radiotherapy (M = 7.46, SD = 6.60). Conclusions: The DS-II has very good psychometric properties and can be recommended as a reliable tool for assessing demoralization in patients with cancer. The results support the implementation of a screening for demoralization in specific risk groups due to significantly increased demoralization scores.